Engine Failure in Axo-Myelinic Signaling: A Potential Key Player in the Pathogenesis of Multiple Sclerosis - Bergaglio, Talia; Luchicchi, Antonio; Schenk, Geert J. (Frontiers in Cellular Neuroscience, 2021)
Multiple Sclerosis (MS) is a complex and chronic disease of the CNS, characterized by both degenerative and inflammatory processes leading to axonal damage, demyelination, and neuronal loss. In the last decade, the traditional outside-in standpoint on MS pathogenesis, which identifies a primary autoimmune inflammatory etiology, has been challenged by a complementary inside-out theory. By focusing on the degenerative processes of MS, the axo-myelinic system may reveal new insights into the disease triggering mechanisms. Oxidative stress (OS) has been widely described as one of the means driving tissue injury in neurodegenerative disorders, including MS. Axonal mitochondria constitute the main energy source for electrically active axons and neurons and are largely vulnerable to oxidative injury. Consequently, axonal mitochondrial dysfunction might impair efficient axo-glial communication, which could in turn affect axonal integrity and the maintenance of axonal, neuronal, and synaptic signaling. In this review, we argue that OS-derived mitochondrial impairment may underline the dysfunctional relationship between axons and their supportive glia cells, specifically oligodendrocytes, and that this mechanism is implicated in the development of a primary cytodegeneration and a secondary pro-inflammatory response (inside-out), which in turn, together with a variably primed host's immune system, may lead to the onset of MS and its different subtypes.